Theoretical Perspectives of the Baltimore Ecosystem Study: Conceptual Evolution in a Social–Ecological Research Project. (26th February 2020) - Pickett, Steward T A; Cadenasso, Mary L; Baker, Matthew E; Band, Lawrence E; Boone, Christopher G; Buckley, Geoffrey L; Groffman, Peter M; Grove, J Morgan; Irwin, Elena G; Kaushal, Sujay S; LaDeau, Shannon L; Miller, Andrew J; et al.
Abstract: The Earth's population will become more than 80% urban during this century. This threshold is often regarded as sufficient justification for pursuing urban ecology. However, pursuit has primarily focused on building empirical richness, and urban ecology theory is rarely discussed. The Baltimore Ecosystem Study (BES) has been grounded in theory since its inception and its two decades of data collection have stimulated progress toward comprehensive urban theory. Emerging urban ecology theory integrates biology, physical sciences, social sciences, and urban design, probes interdisciplinary frontiers while being founded on textbook disciplinary theories, and accommodates surprising empirical results. Theoretical growth in urban ecology has relied on refined frameworks, increased disciplinary scope, and longevity of interdisciplinary interactions. We describe the theories used by BES initially, and trace ongoing theoretical development that increasingly reflects the hybrid biological–physical–social nature of the Baltimore ecosystem. The specific mix of theories used in Baltimore likely will require modification when applied to other urban areas, but the developmental process, and the key results, will continue to benefit other urban social–ecological research projects.